2008
DOI: 10.1017/s0814062600000550
|View full text |Cite
|
Sign up to set email alerts
|

A Student Teacher's Personal Pathway to Education for Sustainability

Abstract: Increasing attention is being given to the inclusion of Education for Sustainability in pre-service teacher education. However, there is little research to explain why and how early-career teachers include Education for Sustainability in their work, or how teacher education providers can encourage and support them to do this. Through analysis of two interviews this paper examines the way in which a pre-service primary school teacher interprets her role in Education for Sustainability. Her personal reflections … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 17 publications
(20 reference statements)
0
18
0
4
Order By: Relevance
“…They stated that they did not see SD as central to either their subject or discipline. As pointed out earlier, teachers' willingness to teach ESD is a very important factor for its implementation and, therefore, it is necessary to overcome this barrier before others are addressed (see Kennelly, Gavrilakis, and Flouri 2008;Shuman and Ham 1997;Pepper and Wildy 2008;Velazques, Manunguia, and Sanchez 2005;Wickman and Sund 2008). Other barriers highlighted by the teachers were a lack of inspiring examples of how to include SD in their teaching and the fact that they and their colleagues lack necessary subject expertise.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They stated that they did not see SD as central to either their subject or discipline. As pointed out earlier, teachers' willingness to teach ESD is a very important factor for its implementation and, therefore, it is necessary to overcome this barrier before others are addressed (see Kennelly, Gavrilakis, and Flouri 2008;Shuman and Ham 1997;Pepper and Wildy 2008;Velazques, Manunguia, and Sanchez 2005;Wickman and Sund 2008). Other barriers highlighted by the teachers were a lack of inspiring examples of how to include SD in their teaching and the fact that they and their colleagues lack necessary subject expertise.…”
Section: Discussionmentioning
confidence: 99%
“…Another important barrier highlighted by half of the teachers who did not include ESD was that they could not see the relevance of ESD to their own teaching. If the teachers do not see the relevance to their subject they will not implement ESD, irrespective of their level of knowledge (see Kennelly, Gavrilakis, and Flouri 2008;Wickman and Sund 2008;Pepper and Wildy 2008). Regardless of the international generality of these barriers, it is important to overcome them in order to increase the implementation of ESD.…”
Section: Discussionmentioning
confidence: 99%
“…The study by Kennelly, Taylor and Maxwell (2008) showed that significant life experiences play an important role in a teacher's commitment to teach education for sustainability (Ef S). These life experiences serve to inculcate values that are retained and reinforced during the teachers' life as a student teacher and intern.…”
Section: Theoretical Underpinningsmentioning
confidence: 99%
“…These life experiences serve to inculcate values that are retained and reinforced during the teachers' life as a student teacher and intern. When teachers care about particular issues, they tend to teach about such issues (Sund & Wickman, 2008, as cited in Kennelly et al, 2008). Kennelly et al's (2008) study also suggests that Ef S-relevant pedagogical content knowledge is important in reinforcing the teacher's determination to implement the teaching of Ef S in school.…”
Section: Theoretical Underpinningsmentioning
confidence: 99%
“…Skamp (2009) developed a typology containing elements of PCK that was used to analyse change in six teachers' pedagogy when using learning landscapes. Kennelly, Taylor, and Maxwell (2008) investigated the type of PCK used by a student teacher in her pre-service education and internship and identified her outdoor experiences and content knowledge as valuable. In a similar way to the Corney and Reid study, neither Skamp nor Kennelly, Taylor, and Maxwell examined these teachers' translation of knowledge into their pedagogy or its subsequent effects on learners.…”
Section: Introductionmentioning
confidence: 99%